Radiation generated by the ultrafast migration of a positive charge following the ionization of a molecular system - Kuleff, Alexander I.; Cederbaum, Lorenz S. (Physical review letters, 2011)
Electronic many-body effects alone can be the driving force for an ultrafast migration of a positive charge created upon ionization of molecular systems. Here we show that this purely electronic phenomenon generates a characteristic IR radiation. The situation when the initial ionic wave packet is produced by a sudden removal of an electron is also studied. It is shown that in this case a much stronger UV emission is generated. This emission appears as an ultrafast response of the remaining electrons to the perturbation caused by the sudden ionization and as such is a universal phenomenon to be expected in every multielectron system.